Effects of graded levels of cottonseed cake on performance, haematological and carcass characteristics of broilers fed from day old to 8 weeks of age. (2007)
Cottonseed cake (CSC) has been used as a cheaper alternative to soyabean cake (SBC) in livestock feeding and a source of dietary protein. There is, however, paucity of information on its nutritive value in chickens. This study evaluated the performance, haematological and carcass characteristics of chickens in which CSC replaced SBC in a nutritional experiment. One hundred and eighty day old chicks (DOC) were fed with 5 different diets, such that 0% (control), 25, 50, 75 and 100% of CSC replaced SBC from day old to 8 weeks of age. Average weekly gains (AWG), feed conversion ratio (FCR) and dressed weight (DWT) were monitored. Blood samples were collected and analyzed for differential white blood cell count (lymphocyte) and haemoglobin (Hb). Data were analysed using descriptive statistics and analysis of variance. Values of AWG and DWT ranged from 0.1 to 0.4 kg and 1.1 to 1.8 kg, respectively, with 100% CSC and control having the least and the highest values among the treatments. FCR ranged from 1.6 to 4.9. Values of lymphocyte and Hb ranged from 35.2 to 54.0% and 8.5 to 11.1 g/dl, respectively. Birds on 75% CSC based diets had blood profile comparable to the control than those of other diets. CSC can replace up to 75% SBC without adverse effects on performance, haematological values and carcass quality of the birds. This reveals CSC as a potent source of protein for meeting the crude protein requirements of chickens.